Distributed Leadership in Elementary School Organizational Development: A Systematic Literature Review on Building Synergy for Shared Vision - Trimuji Handana (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the distributed leadership model in elementary school organizational development, focusing on how synergy among principals, teachers, and education personnel contributes to realizing a shared vision. A Systematic Literature Review (SLR) was conducted, synthesizing findings from 15 peer-reviewed articles published between 2021 and 2026, sourced from Scopus, Web of Science, and ERIC databases. The results reveal that effective distributed leadership in elementary schools is characterized by (1) deliberate delegation of authority and responsibility, (2) cultivation of teacher leadership and collective efficacy, (3) establishment of trust-based relationships, and (4) alignment of school vision with collaborative practices. Key findings indicate that distributed leadership positively influences teacher professional development, instructional quality, and organizational outcomes, often mediated by professional learning communities and teacher collaboration. The novelty of this study lies in its integrated framework for building functional synergy among three key actor groups in elementary school contexts. Practically, the findings offer principals actionable strategies for transitioning from hierarchical management to collaborative leadership and provide policymakers with evidence-based guidance for designing professional development programs focused on distributed leadership competencies.